La responsabilidad social de las empresas que prestan servicio turístico de hospedaje de la ciudad de Yurimaguas - Arirama Caritimari, Mary (2023)
The thesis "The Social Responsibility of companies that provide tourist accommodation services in the city of Yurimaguas", has the purpose of studying the company from the actions of social commitment, this new variable is used in the business field, it addresses four indicators: preservation of the environment, quality of life, the company's commitment to the community and business ethics. The methodology used has a quantitative approach with a descriptive, transactional design. The Survey data collection instrument was used, made up of sociodemographic data and a questionnaire, it was submitted to the reliability test, obtaining Cronbach's Alpha, α = 0.887, therefore, it is a highly reliable instrument. The sample was non-probabilistic of 26 surveys applied to officials who make decisions at the hotel in the city of Yurimaguas. The hypothesis was demonstrated, accepting it because the statistics corroborate it with very significant evaluations.